Time Management Effectiveness Toward Employee Stress Level During Pandemic Covid-19 - Novita Tri Wardani; Amaliyah Amaliyah (Bulletin of Counseling and Psychotherapy, 2022)
Several countries in the world have entered the stage of globalization, and more and more human resources are needed to adapt to the modernization process. Therefore, human resources play an essential role in the sustainability of life today and tomorrow. However, all activities are carried out online due to the increasing pandemic. It makes all individuals experience work stress. This study aims to determine the effectiveness of implementing time management on employees during a pandemic on the level of work stress experienced by new and other situations so that adjustments must be made to these circumstances. This study used descriptive research with a quantitative approach. The study results showed that 23.5% experienced mild stress and 76.5% experienced moderate stress, and none experienced severe stress. Therefore, the application of good time management can reduce the level of work stress experienced by respondents. The application of time management is to be effective because it has fulfilled five aspects, namely planning, prioritizing, avoiding multitasking, avoiding things that are not important, and setting time limits.